Identification and involvement of ferritin in the response to pathogen challenge in the abalone, Haliotis diversicolor. (July 2016) - He, Jian; Jiang, Jingzhe; Gu, Lu; Zhao, Manman; Wang, Ruixuan; Ye, Lingtong; Yao, Tuo; Wang, Jiangyong
Abstract: Accumulating data has demonstrated that ferritin plays an important role in host defense responses against infection by pathogens in many organisms. In this study, ultracentrifugation was used to isolate ferritin from abalone, Haliotis diversicolor, and sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) analysis revealed that this ferritin consisted of two subunits (designated as HdFer1 and HdFer2). There are no disulfide bonds between the HdFer1 and HdFer2 subunits; however, these subunits co-assemble to form heteropolymers. A novel ferritin subunit (HdFer2) was cloned from H. diversicolor by 5ʹ and 3ʹ RACE (rapid amplification of cDNA ends) approach. The full-length HdFer2 cDNA sequence consists of 878 bp with an open reading frame of 513 bp that encodes a protein that is 170 amino acids in length. Quantitative real-time PCR analysis revealed that HdFer1 and HdFer2 were transcribed in various tissues, such as the mantle, gill and hepatopancreas, with the highest levels of expression in the hepatopancreas. Following a challenge with the pathogen, Vibrio harveyi, the expression of HdFer1 and HdFer2 were markedly induced at different times. This study has identified a novel ferritin subunit in H. diversicolor which will contribute to further exploration of the role of ferritin in mollusk innate immune defense against invading pathogens. Highlights: We extracted and purified ferritin from abalone Haliotis diversicolor. A novel ferritin gene HdFer2 was cloned and characterized from H. diversicolor. HdFer transcript levels were altered in abalones upon Vibrio harveyi challenge. HdFer may play an important role in abalone innate immune defense against invading pathogens.